Price Transmission Dynamics and Market Efficiency in Thailand's Cassava Value Chain - Duangbootsee, Uchook (Journal of Applied Economics and Management Strategy, 2024)
Price transmission dynamics in Thailand's cassava value chain have significant implications for market efficiency and the economic stability of farmers. This research focuses on these dynamics, highlighting the limited diversification in recent years. Using vector error correction models (VECM) to analyze price transmission, the study examines the price relationships and adjustments within the cassava chain from farmgate to wholesale and export levels. The analysis is based on monthly price data from January 2003 to January 2023. The study finds strong long-term price correlations but slow adjustments, indicating market inefficiency. Farmgate prices are influenced by wholesale and export prices of cassava products, but not vice versa. This asymmetry causes farmers to face revenue volatility without affecting downstream prices. Additionally, export prices react to wholesale changes, but wholesale prices remain unaffected by other market levels. Factors such as the limited number of processors, trade dependency, and variability in starch quality may contribute to these pricing patterns. Recommendations for improving market efficiency include diversifying cassava products, expanding export markets, empowering farmers through value-added processing, and providing credit to manage surplus supplies.